Origin of Condensation Nuclei in the Springtime Polar Stratosphere - Toon, Owen B.; Turco, Richard P.; Zhao, Jingxia (1995)
An enhanced sulfate aerosol layer has been observed near 25 km accompanying springtime ozone depletion in the Antarctic stratosphere. We use a one-dimensional aerosol model that includes photochemistry, particle nucleation, condensational growth, coagulation, and sedimentation to study the origin of the layer. Annual cycles of sunlight, temperature, and ozone are incorporated into the model. Our results indicate that binary homogeneous nucleation leads to the formation of very small droplets of sulfuric acid and water under conditions of low temperature and production of H2SO4 following polar sunrise. Photodissociation of carbonyl sulfide (OCS) alone, however, cannot provide sufficient SO2 to create the observed condensation nuclei (CN) layer. When subsidence of SO2 from very high altitudes in the polar night vortex is incorporated into the model, the CN layer is reasonably reproduced. The model predictions, based on the subsidence in polar vortex, agree with in situ measurements of particle concentration, vertical distribution, and persistence during polar spring.